The association of serum vitamin D concentration and ventricular dysfunction among patients with acute coronary syndrome - Khademvatani K; Mohammadzad MS; Yekta Z; Hadizadeh O (Dove Medical Press, 2017)
Kamal Khademvatani,1 Mirhosein Seyed Mohammadzad,1 Zahra Yekta,2 Omid Hadizadeh1 1Department of Cardiology, Shohada Hospital, 2Department of Community and Preventive Medicine, Urmia University of Medical Sciences, Urmia, Iran Objective: To determine if vitamin D deficiency was associated with higher odds of left ventricular dysfunction among patients with acute coronary syndrome (ACS) and, if so, to determine whether this association was mediated by increased inflammation as measured by C-reactive protein (CRP) and white blood cell count (WBC). Methods: This was a cross-sectional study of 170 participants with ACS. Multiple logistic regression was used to examine the association between the outcome of ventricular performance and serum vitamin D concentrations. We also determined whether CRP and WBC meet standard criteria as the mediators between left ventricular ejection fraction and vitamin D deficiency. Results: Participants with vitamin D deficiency were more likely to have ventricular dysfunction (OR: 2.12, 95% CI: 1.2–5.23). WBC counts did not meet one of the criteria for mediation. However, the WBC was an effect modifier such that the association of vitamin D deficiency and ventricular dysfunction was only present among participants with WBC more than 11,000. Conclusion: This study found that vitamin D deficiency was associated with higher odds of ventricular dysfunction. Further longitudinal and experimental studies are necessary to confirm this finding and to determine if there is a role for vitamin D supplementation therapy in preventing ventricular dysfunction in select patient populations. Keywords: ventricular dysfunction, vitamin D deficiency, acute coronary syndrome, ejection fraction